1996
DOI: 10.1046/j.1365-2796.1996.43869000.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyperkalaemia induced by trimethoprim in combination with an angiotensin‐converting enzyme inhibitor in a patient with transplanted lungs

Abstract: A 40-year-old woman with transplanted lungs developed life threatening hyperkalaemia (6.8 mmol L-1) during high dose treatment with trimethoprim-sulfamethoxazole for Pneumocystis carinii pneumonia. Trimethoprim has an amiloride-like effect on the distal nephron and may thus induce hyperkalaemia, particularly if other contributing factors coexist. The present patient was also treated with the angiotensin-converting enzyme (ACE) inhibitor enalapril, and the combination of ACE-inhibition and potassium-sparing diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…competitive inhibition of the renal tubular secretion. Besides this effect, trimethoprim can also cause hyperkalaemia [34,35]. Cotrimoxazole and trimethoprim can also induce real renal toxicity: acute tubular necrosis and acute interstitial nephritis are reported [7,36,37].…”
Section: Trimethoprimmentioning
confidence: 99%
“…competitive inhibition of the renal tubular secretion. Besides this effect, trimethoprim can also cause hyperkalaemia [34,35]. Cotrimoxazole and trimethoprim can also induce real renal toxicity: acute tubular necrosis and acute interstitial nephritis are reported [7,36,37].…”
Section: Trimethoprimmentioning
confidence: 99%
“…We have previously shown that the use of co-trimoxazole with angiotensin converting enzyme inhibitors or angiotensin receptor blockers results in an almost sevenfold increase in the risk of hyperkalemia related hospital admission relative to amoxicillin. 14 Case reports show that this drug interaction can cause life threatening hyperkalemia, 15 16 but whether it can increase the risk of sudden death in clinical practice is unknown. This is an important question, because sudden death due to hyperkalemia in the pre-hospital setting is likely to be misattributed to intrinsic heart disease, particularly in older patients with existing cardiovascular disease or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Calcineurin inhibitors, such as cyclosporine or tacrolimus, are associated with as high as a 73% incidence of hyperkalemia 36–37 . Finally, trimethoprim/sulfamethoxazole (Bactrim) has been associated with the development of hyperkalemia 38–39 . Trimethoprim reduces renal K + excretion through the competitive inhibition of epithelial Na + channels in the distal nephron in a manner identical to the K + ‐sparing diuretic, amiloride.…”
Section: Concomitant Medications/conditionsmentioning
confidence: 99%